Neuropsychological assessment in the Israeli healthcare system: a practitioners' survey - Gitit Kavé; Ayala Bloch; Adi Shabi; Sari Maril (BMC, 2020)
Abstract Background The current study examines self-reported professional practices and attitudes of Israeli neuropsychologists, in an attempt to understand how they contribute to funding of neuropsychological assessment (NPA) through the Israeli healthcare system. Methods Two hundred seventy-nine neuropsychologists (176 board-certified experts and 103 interns) participated in an online survey that targeted characteristics of NPA practice in Israel, attitudes toward NPA, and familiarity with healthcare referral procedures. Results Overall, 68% of respondents conducted NPA, with a smaller proportion of experts (56%) doing so than interns (88%). The most common purpose of NPA was to provide treatment recommendations, and respondents listed indications for NPA that matched indications for neuropsychological rehabilitation. Almost two thirds of respondents reported that none of the NPAs that they performed received healthcare funding. While all practitioners believed that the healthcare system should fund NPA, the majority demonstrated lack of familiarity with referral procedures. Conclusions To increase referral rates and create effective neuropsychological services within the Israeli healthcare system, neuropsychologists should work more closely with physicians in integrated care teams. In addition, they should engage in greater advocacy activities that will emphasize the need for publicly funded NPA.